Root resection - Exploring ways beyond extraction - Monika Pal; Santhosh Kumar; G Pratibha (Wolters Kluwer Medknow Publications, 2020)
One of the crucial challenges that any present-day general dentist confronts is the treatment determination between extracting a tooth and placement of a dental implant or by conserving the natural tooth with an interdisciplinary approach. The rising concern amongst the patients towards preserving their dentition has driven the clinicians towards providing treatment options that are more appropriate and conservative and at the same time does not hamper its functional needs. This report highlights one such way of preserving the periodontally compromised natural tooth with just resecting the diseased part of it and also conserving the proprioceptive capacity of the tooth. One-year of regular follow up and maintenance paving way to a healthy periodontium and complete resolution of mobility concerning the affected tooth is described. This report also provides information on root resection in a mandibular molar as a viable and a definitive treatment modality, providing better access to the remaining tooth structure and thereby enabling successive prosthetic rehabilitation.